Video gaming and gaming addiction in transgender people: an exploratory study - Arcelus, Jon; Bouman, Walter Pierre; Richards, Christina; Jimenez-Murcia, Susana; Griffiths, Mark (Akadémiai Kiadó, 2017)
Background: There is anecdotal clinical evidence that transgender people use the online world – such as forums and online video gaming – for the purpose of experiencing their gender identity in a safe, non-threatening, non alienating, nonstigmatizing, and non-critical environment. Aims: To describe the type and degree of gaming behaviour in a comparatively large group of transgender people accessing transgender health services, and to investigate the main predictors of problematic gaming behaviour, focussing on several variables linked to social and interpersonal skills. Methods: Every individual referred to a national transgender health service in the United Kingdom (UK) during an 12-month period was invited to complete a series of questionnaires to measure interpersonal functioning, severity of autistic features, and anxiety and depressive symptoms. Results: A total of 245 people agreed to participate in the study with 154 (62.9%) describing themselves as current gamers. Gaming behaviour in the transgender population attending transgender health services was prevalent, but less than 1% of them presented with clinical scores for Internet Gaming Disorder with no differences according to gender. Problematic gaming behaviour was best predicted by general interpersonal problems, problems socialising, autistic behaviour, anxiety, and depression. Discussion and conclusions: If gaming is used by transgender individuals as a way to cope with anxiety levels and avoid social contact, then gaming which has been designed for this purpose may also be used positively to target those deficits and prepare the person for a successful transition.